Age-stratified association of blood pressure with albuminuria and left ventricular hypertrophy in patients with hypertension and diabetes mellitus - Wei Zhang; Chang-Yuan Liu; Li-Nong Ji; Ji-Guang Wang; for the ATTEND Investigators (Blood Pressure, 2021)
Purpose We investigated associations of blood pressure (BP) with albuminuria and left ventricular hypertrophy (LVH) in young, middle and older aged patients with hypertension and/or diabetes mellitus. Materials & Methods Study participants were treated patients with hypertension or diabetes, enrolled in a China nationwide registry. The 2510 patients were classified into young (<45 years, n = 345), middle (45–64 years, n = 1383) and older (≥65 years, n = 782) age groups. Clinic BP was measured three times consecutively on each of the two clinic visits. These six readings were averaged for analyses. Albuminuria was defined as a urinary albumin-to-creatinine ratio of ≥30 mg/g. LVH was assessed by the electrocardiogram (ECG) Cornell product and voltage methods. Results The prevalence of albuminuria and ECG-LVH was 17.8 and 6.5%, respectively. Mean (±SD) systolic/diastolic BP was 132.0 ± 16.5/85.2 ± 11.9 mmHg, 136.8 ± 17.9/81.7 ± 11.2 mmHg, and 139.8 ± 16.7/75.8 ± 10.4 mmHg in the young, middle and older age groups. In the young age group, the prevalence of albuminuria increased from 8.8% in systolic/diastolic BP <120/80 mmHg to 14.6, 16.0% and 16.5% in 120–129/80–84, 130–139/85–89 and ≥140/90 mmHg, respectively. The corresponding values were 8.9, 7.0, 18.1 and 22.2%, respectively, in the middle age group, and 21.2, 15.5, 16.4 and 24.4%, respectively, in the older age group. Adjusted analyses confirmed the J-shaped relation between BP and albuminuria in the older but not young age group. The prevalence of ECG-LVH was significantly (p for trend ≤0.04) higher with increasing BP similarly in all age groups. Conclusions The association between BP and organ damage seems to differ in young, middle and older aged patients for albuminuria but not ECG-LVH.